2010
DOI: 10.1016/j.neuron.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ligase Nedd4 Promotes Axon Branching by Downregulating PTEN

Abstract: SummaryRegulated protein degradation via the ubiquitin-proteasome system (UPS) plays a central role in building synaptic connections, yet little is known about either which specific UPS components are involved or UPS targets in neurons. We report that inhibiting the UPS in developing Xenopus retinal ganglion cells (RGCs) with a dominant-negative ubiquitin mutant decreases terminal branching in the tectum but does not affect long-range navigation to the tectum. We identify Nedd4 as a prominently expressed E3 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 77 publications
10
174
2
1
Order By: Relevance
“…The regulation of a subset of substrates must be coordinated to balance parallel regulatory pathways in neuronal differentiation or development. For example, Nedd4-1 ubiquitinates and thereby regulates Rap2 during dendrite development 97 and may, at the same time, control axon branching by ubiquitinating PTEN 98 . It is obvious that such regulatory pathways must be properly adjusted in order to achieve proper neuronal network formation.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of a subset of substrates must be coordinated to balance parallel regulatory pathways in neuronal differentiation or development. For example, Nedd4-1 ubiquitinates and thereby regulates Rap2 during dendrite development 97 and may, at the same time, control axon branching by ubiquitinating PTEN 98 . It is obvious that such regulatory pathways must be properly adjusted in order to achieve proper neuronal network formation.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense morpholino oligomers were diluted to a concentration of 1 mM. The xDicer-MO and Pten-MO have been previously published (11,36). The Ins-MO and Igf2-MO were tested using GFP fusion protein constructs (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Calpain is also expressed in the Xenopus spinal cord and its activity is regulated by calcium transients . It has also recently been shown that Nedd4, an E3 ubiquitin ligase, is necessary to turn off PTEN, causing an increase in PI3K signalling and inducing axon branching in Xenopus retinal ganglion cells (Drinjakovic et al, 2010). In a concomitant paper, the knockout of Nedd4-1 in mice showed that Nedd4 is necessary for dendrite arborisation and neurite growth (Kawabe et al, 2010).…”
Section: Research Articlementioning
confidence: 99%